Respiratory support in children. Issue 5 (May 2019) - Bhalla, Anoopindar K.; Newth, Christopher J.L.; Khemani, Robinder G.
Abstract: Respiratory failure is defined by the inability of the respiratory system to adequately deliver oxygen or remove carbon dioxide from the pulmonary circulation resulting in hypoxemia, hypercapnia or both. A wide variety of disease processes can lead to respiratory failure in children. Multiple interventions can support the paediatric patient with respiratory failure, from simple oxygen delivery devices to high frequency oscillatory ventilation and extracorporeal membrane oxygenation. This article will review available devices to improve oxygenation and ventilation, their advantages and disadvantages, and help guide physicians in the management of children with respiratory failure.